Autologous stem cell transplantation improves quality of life in economically challenged, brazilian multiple myeloma patients (Clinics, 2011)
OBJECTIVES: 1) To characterize the impact of multiple myeloma on the quality of life of patients treated in two public institutions in São Paulo State, Brazil, using a generic Short Form 36 Health Survey and a questionnaire specific for oncologic patients (QLQ-C30) upon diagnosis, after the clinical treatment, and at day +100 after autologous stem cell transplantation; 2) to evaluate whether autologous stem cell transplantation can improve the quality of life of our economically challenged population aside from providing a clinical benefit and disease control. METHODS: We evaluated 49 patients with multiple myeloma (a total of 70 interviews) using the two questionnaires. The scores upon diagnosis, post-treatment/pre-autologous stem cell transplantation, and at D+100 were compared using ANOVA (a comparison of the three groups), post hoc tests (two-by-two comparisons of the three groups), and paired t-tests (the same case at two different times). RESULTS: Of the included patients, 87.8% had a family budget under US $600 (economic class C, D, or E) per month. The generic Short Form 36 Health Survey questionnaire demonstrated that physical function, role-physical, and bodily pain indices were statistically different across all three groups, favoring the D+100 autologous stem cell transplantation group (ANOVA). The questionnaire specific for oncologic patients, the QLQ-C30 questionnaire, confirmed what had been demonstrated by the Short Form 36 Health Survey with respect to physical function and bodily pain, with improvements in role functioning, fatigue, and lack of appetite and constipation, favoring the D+100 autologous stem cell transplant group (ANOVA). The post hoc tests and paired t-tests confirmed a better outcome after autologous stem cell transplantation CONCLUSION: The questionnaire specific for cancer patients seems to be more informative than the generic Short Form 36 Health Survey questionnaire and reflects the real benefit of autologous stem cell transplantation in the quality of life of multiple myeloma patients in two public Brazilian institutions that provide assistance for economically challenged patients.